Cigarette smoking and associated factors among men in five South Asian countries: A pooled analysis of nationally representative surveys. - Md Shariful Islam; Mamunur Rashid; Monaemul Islam Sizear; Raafat Hassan; Mahbubur Rahman; Sarker Masud Parvez; Shuvon Chandra Hore; Rehnuma Haque; Farjana Jahan; Supta Chowdhury; Tarique Mohammad Nurul Huda; K M Saif-Ur-Rahman; et al. (PLoS ONE)
Smoking is one of the leading causes of premature deaths worldwide. The cigarette is the commonest form of tobacco smoking. This study investigated the factors associated with cigarette smoking among men in five South Asian countries. We analyzed nationally representative cross-sectional study (Demographic and Health Survey) data conducted in Afghanistan, India, Maldives, Nepal, and Pakistan from 2015-2018. Our study population was men aged between 15 and 49 years. The outcome variable was the prevalence of cigarette smoking. We performed both pooled and country-specific analyses using multivariable logistic regression. The prevalence of cigarette smoking among men is the highest (41.2%) in the Maldives and the lowest (20.1%) in Pakistan. Our pooled analysis found that higher age, lower education, lower wealth status, and involvement in any occupations were strongly associated with cigarette smoking (p-value <0.001). However, we did not find a significant association between age and wealth status in Afghanistan, occupations in Nepal and Pakistan, and education in Pakistan with cigarette smoking when country-specific analyses were performed. In this study, socioeconomic position, age, and urban area are strongly associated with cigarette smoking in South Asian countries. The country-specific circumstances should be considered in planning and designing national smoking control strategies and interventions. However, improving access to smoking cessation services could be an effective intervention for all studied countries, Afghanistan, India, Maldives, Nepal, and Pakistan.